The 27th IUPAC International Conference on Chemistry Education (ICCE 2024) - Tantayanon Supawan; Limpanuparb Taweetham (Chemistry Teacher International)
We are pleased to present this special issue of the Chemistry Teacher International, showcasing a selection of 15 impactful papers from the 27th IUPAC International Conference on Chemistry Education (ICCE 2024), held from July 15-19, 2024, at the Royal Cliff Grand Hotel in Pattaya, Thailand. The conference was organized by the Chemical Society of Thailand, in partnership with Chulalongkorn University, Thammasat University, and Burapha University. An introduction to the papers along with the background of the conference is given.